A review of surgical and audiological outcomes of bonebridge at tertiary centres in Malaysia - Tang, Ing Ping; Ling, Xiu Ngui; Narayanan, Prepageran (Malaysian Citation Centre, 2018)
Objectives: To investigate the surgical and audiological outcome of Bonebridge (BB) at tertiary centres in Malaysia. Study Design: Prospective, intra-subject repeated measurements of which each subject is his/her own control, from year 2012 to 2016 at two tertiary referral centres. Methods: Twenty patients with hearing loss who fulfilled criteria for BB and showed good response to bone conduction hearing aid trial were included. Implantations of BB were carried out under general anaesthesia with preoperative computed tomography (CT) planning. Complications were monitored up to six months postoperatively. Subjects’ audiometric thresholds for air conduction, bone conduction and sound field at frequencies of 250Hz to 8kHz were assessed preoperatively and at six months postoperatively. Subjects’ satisfaction was evaluated at 6 months post operatively with Hearing Device Satisfaction Scale (HDSS) questionnaire. Results: There was no major complication reported. Mean aided sound field thresholds showed significant improvement for more than 30dB from 500 to 4000kHz (p<0.05). There was no significant change in mean unaided air conduction and bone conduction thresholds pre and post operatively from 500 to 4000kHz, with a difference of less than 5dB (p>0.05). All the patients were very satisfied (>80%) with the implant, attributing to the promising functional outcome and acceptable cosmetic appearance. Conclusions: BB implantation surgery is safe and is effective in restoring hearing deficits among patients aged five and above with conductive or mixed hearing loss and single-sided hearing loss